Hepatic Oxidative Stress and Haematological Parameters of Wistar Rats Following Infusion of Carbon Tetrachloride and Treated with Raw and Hydrothermal Processed Herbs - Ojiako, Okey Alphonsus; Chikezie, Paul Chidoka; Ukairo, Doris Ifeyinwa; Ibegbulem, Chiedozie Onyejiaka; Nwaoguikpe, Reginald Nwazue (Pharmacognosy Communications)
Background and Aim: The present study evaluated hepatic oxidative stress and haematological parameters of Wistar rats following infusion of carbon tetrachloride (CCl4) and treatment with extracts of raw and hydro- thermal processed Monodora myristica (Gaertn.), Chromolaena odorata (Linn), Buccholzia coriacea (Engl.) and Sphenostylis stenocarpa (Hochst ex A. Rich). Materials and Methods: Hydrothermal processing of the herbs was according to indigenous traditional methods. Quantitative compositions of alkaloids, flavonoids, tannins and saponins of the herbal extracts were measured using standard methods. Fibrosis was induced in the rats by single dose intra-peritoneal (i.p) injection of CCl4 in paraffin oil as vehicle {1:1 v/v; dose = 1.0 mL/kg body weight (b.wt.)} for 2 consecutive days. The rats received treatments (dose = 250 mg/kg b.wt.; i.p. of the herbal extracts and silymarin or otherwise 1.0 mL/kg b.wt.; i.p. of phosphate buffered saline solution, paraffin oil and CCl4/paraffin oil mixture) for 28 consecutive days. Liver homogenates were measured for malondialdehyde (MDA) content, catalase (CAT) and superoxide dismutase (SOD) activities as well as haematological parameters using spectrophotometric methods. Results: Hydrothermal processing of the raw herbs resulted in losses in their contents for all measured phytochemical classes except for saponins content. The administration of raw and hydrothermal processed herbal extracts reversed the changes in hepatic MDA contents, CAT and SOD activities as well as haematological parameters in the fibrotic rats. Conclusion: Hydrothermal processing of the raw herbs did not adversely affect their capacities to ameliorate hepatic oxidative stress and haematological disorders in the fibrotic rats.
Keywords: Carbon tetrachloride; Catalase; Haematological parameters; Malondialdehyde; Oxidative stress; Superoxide dismutase.